Adaptive Gaze Behavior and Decision Making of Penalty Corner Strikers in Field Hockey - Klatt, Stefanie; Noël, Benjamin; Schwarting, Alessa; Heckmann, Lukas; Fasold, Frowin (Frontiers in Psychology, 2021)
In recent years, studies have increasingly dealt with the interaction of gaze behavior and decision making of team sports athletes. However, there is still a variety of important game situations, for example, in the case of penalty corners in field hockey, in which this interaction has not been investigated in detail yet. Penalty corners present a meaningful goal scoring opportunity by providing a relatively free shot. This paper considers two studies. The first study investigated a possible connection between the gaze behavior and the quality of decisions of experienced field hockey players and evaluated the level of success of different gaze strategies. A preliminary study (Study 1) was designed as a survey questionnaire with the aim of preparing for the main study by obtaining subjective assessments of the individual gaze behavior and decision making of professional athletes. In the second and the main study (Study 2), the gaze behavior of experienced field hockey players was recorded using mobile eye-tracking systems to analyze different strategical approaches in associated gaze behavior and decision making. Study 1 showed that players consider reacting to the defenders' behavior during a penalty corner a promising avenue for improving success at penalty corner attempts. It also indicated that such defense-dependent strategies are currently only rarely employed. Study 2 demonstrated how gaze behavior differs between different strategical approaches of the offense. It was shown that the gaze direction on the ball, the stopper, and the goal area is important to allow for a more optimal adaptation to the tactical behavior of defense. It can be concluded that adaptive decision making (i.e., choosing which variation will be carried out just after the “injection” of the ball) seems promising but requires further training to improve the success rate of penalty corner.